4CPS-234 Pharmacist interventions in neonatal intensive care unit and associated cost avoidance and cost savings. (March 2019) - Kim, Y; Rho, J; Suh, Y; Choi, K; Lee, E; Lee, E; Choi, CW
Abstract : Background: In neonates, frequent changes in dosing intervals and dosage can increase the risk of medication errors. In addition, patients in the Neonatal Intensive Care Unit (NICU) are highly dependent on total parenteral nutrition (TPN), which is one of the most important interventions made by pharmacists. Although the role of ICU pharmacists in improving clinical outcomes has been documented, there are currently few reports on the economic impact of such interventions in this country. Purpose: The purpose of this study was to analyse interventions made by a NICU pharmacist and describe the economic impact by calculating cost avoidance and cost savings associated with accepted interventions. Material and methods: From 1 March to 31 August 2016, a retrospective evaluation was conducted by analysing clinical intervention records from prescription review, TPN consults and Clinical Pharmacokinetic Consultation Service reports delivered by pharmacists in a tertiary hospital. Interventions were graded based on probable outcome severity by three independent pharmacist evaluators. This grade was used to calculate cost avoidance. Cost avoidance and cost saving from accepted clinical interventions were calculated to show the economic impact of NICU pharmacists. Results: During the study period, a total of 608 clinical interventions were performed, TPN was involved in 482 (79.3%) interventions and the number of intervention activities related to prescription review was 81 (13.3%). The most frequent interventions related to prescription review were 'incorrect dose and interval (46.1%)', followed by 'incorrect administration schedule' and 'consult for medication information and treatment plan'. The prescriber's acceptance rate of pharmacist recommendations was 95.2%. Over the 6 months, total cost avoidance was 175, 863, 624 won and total cost saving was 75 033 won. Conclusion: This study showed the impact of a NICU pharmacist on medication safety and costs in a tertiary hospital. However, further study is needed to demonstrate the clinical pharmacist's contribution to the improvement of clinical and economic outcomes more comprehensively. References and/or acknowledgements: 1. Alan HM, Kenneth JS, Julie AP, et al. Cost savings and avoidance from clinical interventions. Am J Health-Syst Pharm 1997;54:392–6. https://www.ncbi.nlm.nih.gov/pubmed/9043561 2. Audrey JL, Maureen SB, Katherine KK, et al. Clinical and economic outcomes of pharmacist recommendations in a Veterans Affairs medical center. Am J Health-Syst Pharm 2002;59:2070–7. http://www.ajhp.org/content/59/21/2070 No conflict of interest.